From near‐zero to zero fluoroscopy catheter ablation procedures. (4th September 2019) - Santoro, Amato; Di Clemente, Francesca; Baiocchi, Claudia; Zacà, Valerio; Bianchi, Claudio; Bellini, Cesare; Falciani, Francesca; Valente, Serafina; Gaspardone, Achille; Lamberti, Filippo
Abstract: Aims: The use of electroanatomical mapping (EAM) systems can reduce radiation exposure (RX) and it can also completely eliminate the use of RX. Radiation exposure related to conventional radiofrequency ablation procedures can have a stochastic and deterministic effect on health. The main aim of this study was to evaluate the safety and feasibility of an entirely nonfluoroscopic approach to catheter ablation (CA) using EAM CARTO3. Methods: In 2011 we started an RX‐minimization programme in all procedures using the CARTO system with the deliberate intention to not resort to the aid of RX unless strictly necessary. We divided procedures into two groups (group 1: from 2011 to 2013; group 2: from 2014 to 2017). The only exclusion criteria were the need for transseptal puncture, and nonidiopathic ventricular tachycardia (VT). Results: From a total of 525 procedures, we performed CA entirely without RX in 78.5% of cases. From 2011 to 2013, we performed CA without RX in 38.5% of cases; from 2014 to 2017, we performed 96.2% of cases with zero RX. The use of RX was significantly reduced in group 2 (group 2: 1.4 ± 19.6 seconds vs group 1: 556.92 ± 520.76 seconds; P < .001). These differences were irrespective of arrhythmia treatment. There were no differences between the two groups in acute success, complications, or duration of procedures. Conclusion: CA of supraventricular tachycardia and VT entirely without RX, guided by the CARTO system, is safe, feasible, and effective. After an adequate learning curve, CA can be performed entirely without RX.